2015
DOI: 10.1021/acs.macromol.5b00251
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[1,2-b:4,5-b′]dithiophene and Thieno[3,4-c]pyrrole-4,6-dione Based Donor-π-Acceptor Conjugated Polymers for High Performance Solar Cells by Rational Structure Modulation

Abstract: A series of benzo­[1,2-b:4,5-b′]­dithiophene and thieno­[3,4-c]­pyrrole-4,6-dione (BDT-TPD) based copolymers (P1–P4) with D-π-A structures are designed and synthesized. When the π bridges change from 2,2′-bithiophene to thieno­[3,2-b]­thiophene and then to 3-hexylthieno­[3,2-b]­thiophene, the performance of the polymer photovoltaic devices shows significant improvement. Especially, the device based on P4 with alkylthienyl-substituted BDT and π bridge of 3-hexylthieno­[3,2-b]­thiophene exhibits power conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…The monomers 1,3‐bis(5‐bromo‐thieno[3,2‐ b ]thiophen‐2‐yl)‐5‐(2‐octyldodec‐yl)‐4 H ‐thieno[3,4‐ c ]pyrrole‐4,6(5 H )‐dione ( A1 ) and 1,3‐bis‐(5‐bromo‐6‐hexylthieno[3,2‐ b ]thiophen‐2‐yl)‐5‐(2‐octyldodec‐yl)‐4 H –thieno[3,4‐ c ]pyrrole‐4,6(5 H )‐dione ( A2 ) were synthesized according to the reported literature . Compounds P5 and P6 were prepared by palladium catalyzed Stille polymerization between A1 / A2 and 4,4‐dioctyl‐2,6‐bis(trimethylstannyl)‐4 H ‐silolo[3,2‐ b :4,5‐ b ′]dithiophene ( B1 ), respectively ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomers 1,3‐bis(5‐bromo‐thieno[3,2‐ b ]thiophen‐2‐yl)‐5‐(2‐octyldodec‐yl)‐4 H ‐thieno[3,4‐ c ]pyrrole‐4,6(5 H )‐dione ( A1 ) and 1,3‐bis‐(5‐bromo‐6‐hexylthieno[3,2‐ b ]thiophen‐2‐yl)‐5‐(2‐octyldodec‐yl)‐4 H –thieno[3,4‐ c ]pyrrole‐4,6(5 H )‐dione ( A2 ) were synthesized according to the reported literature . Compounds P5 and P6 were prepared by palladium catalyzed Stille polymerization between A1 / A2 and 4,4‐dioctyl‐2,6‐bis(trimethylstannyl)‐4 H ‐silolo[3,2‐ b :4,5‐ b ′]dithiophene ( B1 ), respectively ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A high PCE of 7.05% was obtained in the PSCs with a thieno[3,2‐ b ]thiophene‐bridged polymer P(BDT‐TT‐BO) as donor . In our previous report, thieno[3,2‐ b ]thiophene (TT) bridge has been proved to be able to enhance the hole mobility and the optoelectronic performances in the BDT‐TPD‐based polymers . It has been demonstrated that the light absorption, energy levels, charge transport, and photovoltaic performances can be efficiently adjusted by introducing different π bridges .…”
Section: Introductionmentioning
confidence: 99%
“…[39,41] Monomer IDT-di-Tin was purchased from SunaTech Inc. [39,41] Monomer IDT-di-Tin was purchased from SunaTech Inc.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…[15,22,[27][28][29][30][31][32][33] Replacing the outward thiophene moiety of IDT with extended thieno[3,2-b]thiophene (TT) unit or inserting πbridges such as thiophene or TT between IDT donor and acceptor units have been proven to be effective strategies to extend π-conjugated system of IDT backboned polymers. [39] Therefore, further rational design and detailed investigation of the length on π-conjugated backbone would be necessary to obtain desirable organic photovoltaic materials. Nevertheless, proper attention needs to be paid to the solubility problems caused by extended fusion, which would cause negative impacts on coating and film morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] Park et al reported a new class of anthracene-thiophene based copolymers incorporating bulky triisopropylsilylacetylene (TIPS) groups at the 9,10-positions of the anthracene moiety. 32 It was reported that the incorporation of TIPS groups overcame the poor charge transportation properties and high crystallinity that are generally associated with polythiophene-based copolymers.…”
Section: -27mentioning
confidence: 99%